Pengujian Fungsionalitas Aplikasi Shopee Menggunakan Metode Black Box Testing dengan Penerapan Teknik Decision Table Testing pada Fitur Checkout - Maulina Mukaromah; Aliya Ratna Ningrum; Dina Hermawati; Chiekan Denanta Alviani; Muhammad Nurfauzi Sahono (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
The checkout feature in e-commerce applications is a critical component that integrates several business processes, ranging from shipping-address validation to payment-method authorization. Functional failures at this stage can significantly reduce transaction conversion rates and erode user trust, particularly because the reliability of digital payment processing is one of the main factors shaping consumer confidence toward e-commerce platforms. This study aims to test the functionality of the checkout feature of the Shopee application using the Black Box Testing approach, specifically the Decision Table Testing technique. This technique was chosen for its ability to systematically map complex condition combinations, and it has been shown to be effective for testing rule-based logic across various types of systems. The testing focused on three main conditions, namely address validation, payment method, and product stock availability, producing eight rule combinations derived from three binary conditions. The results show that Decision Table Testing successfully uncovered functional bugs in certain transactional scenarios, especially in double negative condition combinations that are difficult to detect using single-condition techniques such as Equivalence Partitioning, thereby providing valid improvement recommendations to preserve user transaction comfort and experience.